THE CRIME OF PORNOGRAPHY ON INTERNET MEDIA - Subekti; Soekorini, Noenik; Sidarta, Dudik Djaya (Faculty of Law, University of Dr. Soetomo, 2017)
The development of the internet gave birth to new problems. Among them appear more sophisticated crime in the form of